2019
DOI: 10.1002/cam4.2117
|View full text |Cite
|
Sign up to set email alerts
|

Survey of dentin sialophosphoprotein and its cognate matrix metalloproteinase‐20 in human cancers

Abstract: Background Matrix metalloproteinases‐20 (MMP20) expression is widely regarded as tooth specific, with expression limited to dental hard tissues. Recently, we reported MMP20 expression and interaction with dentin sialophosphoprotein (DSPP), a member of the Small Integrin Binding Ligand N‐linked Glycoproteins (SIBLINGs), in human oral squamous cell carcinoma (OSCC) and dysplastic oral premalignant lesions (OPLs), suggesting a role for MMP20‐DSPP interaction in oral carcinogenesis. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…First, a 64-year-old man with colorectal polyposis and dentinogenesis imperfecta with a finding of NM_014208.3 (DSPP):c.52G>T (p.Val18Phe). DSPP gene has been previously linked to oral cancers ( Joshi et al, 2010 ), but MMP20-DSPP co-localization and interaction has been observed in breast, colorectal and other cancers as well ( Aseervatham et al, 2019 ). TSO/TSOE was also used to diagnose a 72-year-old woman who had had ascending colon adenocarcinoma at the age of 64 and with a family history of muscle disease; a known familial CHEK2 variant NM_007194.3(CHEK2):c.319+2T>A p.?…”
Section: Resultsmentioning
confidence: 99%
“…First, a 64-year-old man with colorectal polyposis and dentinogenesis imperfecta with a finding of NM_014208.3 (DSPP):c.52G>T (p.Val18Phe). DSPP gene has been previously linked to oral cancers ( Joshi et al, 2010 ), but MMP20-DSPP co-localization and interaction has been observed in breast, colorectal and other cancers as well ( Aseervatham et al, 2019 ). TSO/TSOE was also used to diagnose a 72-year-old woman who had had ascending colon adenocarcinoma at the age of 64 and with a family history of muscle disease; a known familial CHEK2 variant NM_007194.3(CHEK2):c.319+2T>A p.?…”
Section: Resultsmentioning
confidence: 99%
“…Aseervatham et al reported that Matrix Metalloproteinase 20 (MMP20) played a tumorigenic role on Oral Squamous Cell Carcinomas (OSCCs) by upregulating the genes related to invasion, metastasis, angiogenesis, and epithelial-mesenchymal transition (EMT) 24 . They also elucidated that MMP20 and its cognate DSPP paring a potential marker of some epithelial cancers 25 . The expression of C18orf26 induced the activation of Akt and sustaining the high proliferation of tumor cells, making it a potential novel therapeutic target 26 .…”
Section: Discussionmentioning
confidence: 99%
“…20 They also elucidated that MMP20 and its cognate DSPP paring a potential marker of some epithelial cancers. 21 The expression of C18orf26 induced the activation of Akt and sustaining the high proliferation of tumor cells, making it a potential novel therapeutic target. 22 Handa et al reported that the high CASP14 expression is associated with proliferation, cancer stemness of breast cancer.…”
Section: Discussionmentioning
confidence: 99%